2018
DOI: 10.1021/acs.jpcc.8b02094
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Investigations of Transition Metal Surface Energies under Lattice Strain and CO Environment

Abstract: An understanding of the relative stability of surface facets is crucial to develop predictive models of catalyst activity and to fabricate catalysts with a controlled morphology. In this work, we present a systematic density functional theory study of the effect of lattice strain and CO environment on the surface formation energies of Cu, Pt, and Ni. First, we show that both compressive and tensile lattice strains favor the formation of stepped versus low-index terraces such as (111) and (100). Then, we invest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 41 publications
1
27
0
Order By: Relevance
“…To comprehensively model CO (2) reduction, we estimated the reaction energetics for various reaction pathways using explicit- solvent simulations. According to recent experimental spectroscopic 25 and computational work 43 , the presence of CO increases the density of highly active, low-coordinated step sites on polycrystalline copper. Given the generally lower activation barriers associated on steps vs. terraces 16,44 , the activity of steps would, from a simple consideration of the Arrhenius equation, dominate the overall activity.…”
Section: Resultsmentioning
confidence: 99%
“…To comprehensively model CO (2) reduction, we estimated the reaction energetics for various reaction pathways using explicit- solvent simulations. According to recent experimental spectroscopic 25 and computational work 43 , the presence of CO increases the density of highly active, low-coordinated step sites on polycrystalline copper. Given the generally lower activation barriers associated on steps vs. terraces 16,44 , the activity of steps would, from a simple consideration of the Arrhenius equation, dominate the overall activity.…”
Section: Resultsmentioning
confidence: 99%
“…The Wulff shapes of the Cu nanoparticles are based on a previous manuscript that followed similar computational steps in creating Wulff shapes. 45 Figure 4D presents the clean Cu particle with various facets. Figure 4E presents the shape after being exposed under a minimal CO partial pressure of around 4.4 3 10 À9 bars.…”
Section: Morphology For Both Samples Was Investigated By Scanning Electron Microscopy (Sem) (Figuresmentioning
confidence: 99%
“…Chan and co-workers performed theoretical investigations of transition metal Cu, Pt, and Ni surface energies under lattice strain and CO environment, in which they have found that the strain effects favor the formation of stepped terraces rather than low index facets such as (111), and the CO environment clearly favors such stepped facets. [93] The two effects above consider the situation where the adsorbate only is bond to one single elemental metal. Ensemble effect, on the other hand, takes into account the interaction with an ensemble of surface atoms.…”
Section: H O H O Oxidation Products H E Anode Reactionmentioning
confidence: 99%